Potential Roles of PTEN on Longevity in Two Closely Related Argopecten Scallops With Distinct Lifespans - Xu, Hanzhi; Lu, Xia; Wang, Chunde; Ning, Junhao; Chen, Min; Wang, Yuan; Yuan, Ke (Frontiers in Physiology, 2022)
Phosphatase and tensin homolog deleted on chromosome ten (PTEN) has been found to regulate longevity through the PI3K/Akt/FoxO pathway and maintenance of genome integrity in worms, flies and mammals. However, limited information is available on the roles of PTEN in longevity of marine animals. Here we extended this paradigm using two closely related Argopecten scallops, A. purpuratus and A. irradians, with significantly distinct life spans, which are commercially important bivalve species for fishery and aquaculture in China, USA, Peru and Chile. The ORFs of the ApPTEN and AiPTEN were 1476 bp and 1473 bp, which encoded 491 and 490 amino acids, respectively. There were 48 synonymous and 16 non-synonymous SNPs and one InDel of three nucleotides between ApPTEN and AiPTEN, resulting in variations in 15 amino acids and lack of S453 in AiPTEN. Differences in conformation and posttranslational modification were predicted between ApPTEN and AiPTEN, which may indicate different activities of ApPTEN and AiPTEN. When the animas were subjected to nutrition restriction, the expression of both ApPTEN and AiPTEN was up-regulated, with AiPTEN responded faster and more robust than ApPTEN. Ionizing radiation induced significantly elevated expression of ApPTNE but not AiPTEN in the adductor muscle, and the mortality rate of A. purpuratus was significantly lower than that of A. irradians, indicating that ApPTNE may play a protective role by maintaining the genome integrity. RNAi of ApPTNE significantly down-regulated the expression of its downstream regulated genes known to favor longevity, such as FoxO, Mn-SOD, and CAT. These results indicated that PTEN may contribute to the longevity of A. purpuratus through regulation of nutrient availability and genomic stability, probably via PI3K/Akt/FoxO pathway. Our study may provide new evidence for understanding of the conservative functions of PTEN in regulation of lifespan in animals and human, and it may also benefit the selection of scallops strains with long lifespan and thus larger size.